Предмет: Математика,
автор: Дакха
1-sin^2 a+ctg^2 a*sin^2 a
Ответы
Автор ответа:
0
cos²α
1 - sin²α + ---------- · sin²α = (1-sin²α)+cos²α= cos²α+cos²α=2cos²α
sin²α
Использовано основное тригонометрическое тождество:
sin²α+cos²α=1 ⇔ 1-sin²α=cos²α
и по определению
cosα cos²α
ctgα = --------- ⇒ ctg²α= ---------
sinα sin²α
1 - sin²α + ---------- · sin²α = (1-sin²α)+cos²α= cos²α+cos²α=2cos²α
sin²α
Использовано основное тригонометрическое тождество:
sin²α+cos²α=1 ⇔ 1-sin²α=cos²α
и по определению
cosα cos²α
ctgα = --------- ⇒ ctg²α= ---------
sinα sin²α
Автор ответа:
0
Немного не понятно
Автор ответа:
0
смотри,я внесла пояснения
Похожие вопросы
Предмет: География,
автор: solomiahalus8
Предмет: Математика,
автор: denisskasirins
Предмет: Математика,
автор: angelinasaeva27
Предмет: Математика,
автор: vbulawkin